Development of Technology-Based Interactive Learning Media in Health Promotion Education - DESIF UPIX USMANINGRUM; Almuhaimin (Poltekkes Kemenkes Jambi, 2025)
Background: The digital transformation of health education requires interactive learning media that canimprove the effectiveness of the student learning process. This study aims to develop technology-basedinteractive learning media in health promotion education.Methods: The research was conducted using the Research and Development (R&D) ADDIE model(Analysis, Design, Development, Implementation, Evaluation) involving 30 students as participants. Themedia developed was audio-visual media for introducing basic multimedia photography and videographyequipment, specifically the Canon M6 Mark II Mirrorless Camera.Results: The results of the needs analysis showed that 92.31% of the students needed technology-basedmedia to support their understanding of the material. The effectiveness evaluation showed a significantincrease in students cognitive scores (p=0.000). Conclusion: This study concluded that audio –visual media as part of interactive learning can improvestudent understanding and has the potential to be integrated into the institution’s digital learning system.